Documenting the digital divide: Identifying barriers to digital mental health access among people with serious mental illness in community settings - Ellen E. Kozelka; Stephanie C. Acquilano; Monirah Al-Abdulmunem; Sue Guarino; Glyn Elwyn; Robert E. Drake; Elizabeth Carpenter-Song (Elsevier, 2023)
The transition to and acceptance of digital mental health tools has been heralded as a paradigm shift for providing and accessing care. Yet, providers and clients express concerns over privacy, efficacy, and personalization, as well as their ability to assess the thousands of available digital tools. In response to these concerns and calls for support to address them, the authors developed the Technology Specialist program. After a successful feasibility study, the research team launched a pilot study in late 2021 amid continuing COVID-19 protocols, presuming the rapid adoption of technology during the pandemic would facilitate the incorporation of the Technology Specialist. Despite the success of the role, the shifts in care delivery at one community mental health center created and exposed barriers to the implementation and uptake of digital tools. In this paper, the authors describe key access barriers exposed through the implementation of the pilot at the client, provider, and organizational levels. These barriers highlight a shifting digital divide for access to digital mental health among people with serious mental illness. The re-framed method of contextual engagement presented here may help direct research and practice toward collaborative and equitable action strategies for long-term success in community health settings.